Performance and stability of sewage sludge digestion under CO2 enrichment: A pilot study. (December 2017) - Alibardi, Luca; Green, Kevin; Favaro, Lorenzo; Vale, Peter; Soares, Ana; Cartmell, Elise; Bajón Fernández, Yadira
Highlights: CO2 enrichment was tested on sewage sludge anaerobic digestion at pilot scale. CO2 enrichment enhanced CH4 production under moderate and intense injections. CO2 injection had no negative effects on anaerobic digestion process stability. Benefits of CO2 enrichment were proved without exogenous H2 addition. Abstract: Carbon dioxide (CO2 ) injection in anaerobic digestion has recently been proposed as an interesting possibility to boost methane (CH4 ) recovery from sludge and organic waste by converting a greenhouse gas into a renewable resource. This research assessed the effects of exogenous CO2 injection on performance and process stability of single-phase continuous anaerobic digesters. Two pilot scale reactors treating sewage sludge were operated for 130 days. One reactor was periodically injected with CO2 while the other acted as control. Two injection frequencies and injection devices were tested. The results indicated that CO2 enrichment allowed an increase in CH4 production of ca. 12%, with a CH4 production rate of 371 ± 100 L/(kgVSfed ·d) and a CH4 concentration of ca. 60% when dissolved CO2 levels inside the test reactor were increased up to 1.9-fold. Results also indicated an improvement in process resilience to temporary overloads and no impacts on stability parameters.